Lesch-Nyhan disease in two families from Chiloé Island with mutations in the HPRT1 gene. (3rd July 2017) - Nguyen, Khue Vu; Silva, Sebastian; Troncoso, Monica; Naviaux, Robert K.; Nyhan, William L.
ABSTRACT: Lesch-Nyhan disease (LND) is a rare X-linked inherited neurogenetic disorder of purine metabolism in which the enzyme, hypoxanthine-guanine phosphoribosyltransferase (HGprt) is defective. The authors report two independent point mutations leading to splicing errors: IVS 2 +1G>A, c.134 +1G>A, and IVS 3 +1G>A, c.318 +1G>A in the hypoxanthine-phosphoribosyltransferase1 ( HPRT1 ) gene which result in exclusion of exon 2 and exon 3 respectively, in the HGprt enzyme protein from different members of two Chiloé Island families. Molecular analysis has revealed the heterogeneity of genetic mutation of the HPRT1 gene responsible for the HGprt deficiency. It allows fast, accurate carrier detection and genetic counseling.